STRATEGI KOMUNIKASI DALAM PELESTARIAN BUDAYA SARONEN KEPADA GENERASI MUDA DI KABUPATEN SUMENEP - Romadhan, Mohammad Insan; Puspaningtyas, Anggraeny; Rahmadanik, Dida (representamen, 2018)
Culture and Indonesia is a thing that will never loose. But cultures that abounds in its development especially in the digital era and the current globalization as pushed the waning cultural premises in indonesia specially in younger generations. It would certainly be the task of the Government as the driving force in cultural preservation efforts. One of the local culture that needs to be preserved is a saronen musical culture derived from the Regency of Sumenep Madura. Based on the phenomenon of researchers interested in knowing the strategies of communication in Cultural preservation Saronen To the younger generation in Sumenep. As for the research methods using a descriptive qualitative approach with data collection techniques of observation, interview and documentation study. The results in this study demonstrate the communication strategy undertaken by the Department of culture, tourism, youth and sports festival by using Sumenep Regency as a medium in the delivery of cultural preservation efforts to saronen generation Young's been right on target.Key Word: Communication Strategy, Saronen Cultural Preservation, The Younger Generation